2018
DOI: 10.1002/pon.4842
|View full text |Cite
|
Sign up to set email alerts
|

A model of identity grounded in the acute season of survivorship

Abstract: The theory that emerged from this study articulates the impact of the early cancer experience on the identity of patients. It also provides a framework for predicting which interventions may improve the cancer experience. Exploring how to best provide information that helps patients re-establish and maintain their routines after diagnosis is an important future direction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 27 publications
(31 reference statements)
0
10
0
Order By: Relevance
“…They identify that HISB serves to “increase predictability” [ 27 ] and may assist with “anticipating the sequence of events” [ 27 ] that will likely take place. These goals of HISB are consistent with the informational need identified in the study leading up to this work: that information is essential to helping individuals know what to expect in the future so that they can effectively plan how to live their lives [ 22 ].…”
Section: Introductionmentioning
confidence: 63%
See 2 more Smart Citations
“…They identify that HISB serves to “increase predictability” [ 27 ] and may assist with “anticipating the sequence of events” [ 27 ] that will likely take place. These goals of HISB are consistent with the informational need identified in the study leading up to this work: that information is essential to helping individuals know what to expect in the future so that they can effectively plan how to live their lives [ 22 ].…”
Section: Introductionmentioning
confidence: 63%
“…In a previous study conducted by the lead author (MT) [ 22 ] it was identified that the diagnosis of malignancy resulted in widespread interruption to the lives of those affected by cancer. This study used grounded theory [ 23 , 24 ] to analyze data from 43 semistructured interviews conducted with 18 patients who had been recently diagnosed with cancer and 15 friends and family in Manitoba, Canada.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The coding process progressed through open, selective and theoretical coding in keeping with methods well described elsewhere [22,23,25]. Data collection, analysis, and drafting of the manuscript was conducted by the first author (MT), a researcher and practicing medical oncologist who has conducted and published previous work employing classic grounded theory methods [28,29]. He has received training in conducting classic grounded theory research as well as qualitative research methods in general at the masters and doctoral level.…”
Section: Methodsmentioning
confidence: 99%
“…In a previous study conducted by the lead author (MT) [22] it was identified that the diagnosis of malignancy resulted in widespread interruption to the lives of those affected by cancer. This study used grounded theory [23,24] to analyze data from 43 semistructured interviews conducted with 18 patients who had been recently diagnosed with cancer and 15 friends and family in Manitoba, Canada.…”
Section: Introductionmentioning
confidence: 99%